Green Banking Pengaruh Green Banking dan Kualitas Audit Terhadap Kinerja Keuangan Perusahaan - Jane, Elza Bertha (Ma Chung Press, 2025)
This study aims to evaluate the influence of green banking implementation and audit quality on the financial performance of banking institutions in Indonesia. Financial performance is measured using Return on Assets (ROA) and Return on Equity (ROE), with firm size included as a control variable. Financial performance serves as a key indicator of a company’s management effectiveness, while green banking reflects the bank’s commitment to environmental sustainability, and audit quality indicates the reliability of financial reporting.The research sample consists of seven banks participating in the Green Banking Pilot Project in Indonesia during the 2017–2023 period, resulting in a total of 49 observations. The analysis was conducted using multiple linear regression based on Partial Least Squares Structural Equation Modeling (PLS-SEM) with the support of SmartPLS 4 software. The findings reveal that green banking has a positive effect on both ROA and ROE, suggesting that the adoption of sustainability principles enhances asset utilization efficiency and increases shareholder returns. Meanwhile, audit quality has a positive effect on ROA but shows no significant impact on ROE, indicating that high-quality external audits can improve operational efficiency but do not necessarily influence equity management directly. The implications of this study emphasize the importance of integrating sustainability practices and reliable auditing mechanisms to improve financial performance, as well as the need for comprehensive managerial strategies to optimize equity returns.